A Comprehensive Literature Review of Cost-Effectiveness of Uterine Tamponade Devices for The Treatment of Postpartum Hemorrhage - Fajar Nurochman Sidik; Dhimas Muhammad Suharyo (International Medical Journal Corp. Ltd, 2024)
Background: The literature on uterine tamponade devices for postpartum hemorrhage (PPH) reveals a complex interplay of efficacy, safety, and cost-effectiveness, particularly in low- and middle-income countries. Their modeling indicates that affordable UBT could significantly mitigate maternal morbidity and mortality, thus addressing a pressing healthcare challenge in resource-limited settings. Literature Review: Further expanding on this topic, (Pingray et al., 2021) conducted a systematic review that synthesizes various studies evaluating the effectiveness of uterine tamponade devices compared to standard care for refractory PPH. Their findings highlight the potential of these devices to reduce the necessity for surgical interventions and enhance maternal survival rates, presenting a strong case for the economic benefits of implementing UBT in clinical practice. Conversely, the article by (D. Weeks et al., 2022) brings a critical lens to the discussion, emphasizing the need for caution in adopting UBT widely. While acknowledging the high success rates associated with UBT, the authors raise concerns about the quality of the evidence, particularly the reliance on nonrandomized studies. They argue that the potential for increased need for further interventions post-UBT use necessitates a careful evaluation of the benefits versus risks. This perspective prompts a reevaluation of the implementation strategies for UBT, advocating for rigorous quality improvement measures within healthcare systems. Conclusion: Together, these articles provide a comprehensive understanding of the cost-effectiveness of uterine tamponade devices for PPH treatment. They highlight the urgent need for accessible interventions while emphasizing the importance of robust evidence and quality standards in their implementation. The discourse suggests that while UBT presents a promising solution, its successful integration into healthcare systems requires careful consideration of safety, efficacy, and the contextual challenges faced in diverse settings.